1999
DOI: 10.1295/polymj.31.28
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Unsaturated Polyester in the Epoxy Matrix System

Abstract: ABSTRACT:A study of the interpenetrating polymer network (IPN) as a polymer blend matrix was carried out using different compositions of unsaturated polyester (UP) to epoxy (EP) resins. It was observed that 5 wt% UP in the blend provides maximum mechanical properties, particularly the impact strength for optimum casting. Fourier transform infrared (FT-IR) spectroscopy was used to investigate the intermolecular hydrogen bonding and functional group change. In this work, changes of physical property, e.g., visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…In early 1960s, Fowkes (18) introduced the concept of surface free energy, γ , which can be resolved into a London dispersive component (superscript L) and a specific (or polar, SP) component (18)(19)(20),…”
Section: Contact Angle Measurementsmentioning
confidence: 99%
“…In early 1960s, Fowkes (18) introduced the concept of surface free energy, γ , which can be resolved into a London dispersive component (superscript L) and a specific (or polar, SP) component (18)(19)(20),…”
Section: Contact Angle Measurementsmentioning
confidence: 99%
“…When the surface free energy of a solid can be determined on the basis of the contact angle measurements using the geometric mean, the work of adhesion, W A , according to Fowkes' proposition (18) based on the solid (subscript S)-liquid (L) droplet-air system, can be described by (19)(20)(21)(22)(23)(24)(25)(26) …”
Section: Surface Free Energy Analysis Using Two-liquid Testsmentioning
confidence: 99%
“…(12,21,26). However, recent studies (27)(28)(29) have shown that using the two liquids according to geometric mean unsatisfactorily gives a significant variety of energetic results when testing liquids are varied within the pair of liquids used, such as with water-diiodomethane, water-ethylene glycol, and diiodomethane-ethylene glycol.…”
Section: Surface Free Energy Analysis Using Two-liquid Testsmentioning
confidence: 99%
“…The addition of unsaturated polyester (UPE) to epoxy to form polymer blends has proven to be beneficial to the overall properties of the prepared composite, especially the impact strength, in an attempt to manufacture high performance composites [4].…”
Section: Introductionmentioning
confidence: 99%